Student-Conducted Research in the Mission of the American Universities versus the Universities in Ukraine - Sbruieva, Alina; Shykhnenko, Kateryna (Journal of History Culture and Art Research, 2020)
The purpose of the study was to analyse the mission statements of the universities from America and Ukraine to identify how student-conducted research is represented in the different types of higher education institutions’ missions. The study utilised the exploratory design and relied on qualitative data drawn from content analysis which were then transformed into quantitative data. The study analysed the content of the mission statements of 46 U.S. leading universities and 10 Ukrainian universities included in a feasible list. The content analysis of mission statements of classical (conventional) universities, corporate universities, public research universities, and ultimate digital learning universities was performed using Voyant Tools. The research occupies the leading position in the missions of corporate universities, public research universities in America, and classical and research universities in Ukraine. The university missions are formulated with regard to the social demand, and political and economic trends in the country and the world. The missions of the American Universities are more diverse than the missions of the Ukrainian universities which suggests that the American universities have more freedoms than the Ukrainian ones. The post-industrial stage of education is at its peak of development in America while in Ukraine it is emerging. The research in Ukraine is conducted by separate research institutions. This supposes that the university (student-performed) research does not get enough attention and support. The American higher education model has become a standard model in Ukraine. Further research is needed to address the legislation loopholes of supporting the research at the universities.